2005
DOI: 10.1149/1.1945729
|View full text |Cite
|
Sign up to set email alerts
|

Microelectrode Array for Isolation of Electrode Polarization on Planar Solid Electrolytes

Abstract: Planar cells incorporating a microelectrode as the working electrode were prepared using materials and techniques commonly employed in fabrication of planar solid oxide fuel cells. Initial results of ac and dc polarization measurements suggest that these cells potentially offer excellent isolation of working electrode frequency response (impedance), and quantification of steady-state current-overpotential relationships. The success of the technique relies heavily on how precisely the geometry of the microelect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 12 publications
(25 reference statements)
0
29
0
Order By: Relevance
“…This is likely related to the presence of small defects in the film, which exist even if the film is denser overall. We also observed a reaction between the mask and ceria, which becomes more serious at higher temperatures [7] .…”
Section: A-3 Development Of Insulating Maskmentioning
confidence: 61%
See 4 more Smart Citations
“…This is likely related to the presence of small defects in the film, which exist even if the film is denser overall. We also observed a reaction between the mask and ceria, which becomes more serious at higher temperatures [7] .…”
Section: A-3 Development Of Insulating Maskmentioning
confidence: 61%
“…A-2(c), pattern B, and the mask and working electrode were assumed to have linear RC characteristics. These calculations showed that a mask resistance of >25 kOhm-cm 2 results in negligible error or distortion of the measured microelectrode impedance [7] .…”
Section: A-3 Development Of Insulating Maskmentioning
confidence: 84%
See 3 more Smart Citations